THE ANALYSIS OF THE INFLUENCE OF BANK INDONESIA CERTIFICATE (SBI), SHARIAH BANK INDONESIA CERTIFICATE (SBIS), INFLATION AND BI RATE ON FUND DISTRIBUTION TO THE MSMEs SECTOR BY SHARIA BANKING IN INDONESIA - Wahyu Lailia Devi; Eko Fajar Cahyono (Universitas Airlangga, 2020)
This research was carried out on two banking sides, the first side was on the conventional side, and the second was on the sharia side. The conventional side was used to describe the influence of Bank Indonesia Certificates (SBI), inflation, and the BI Rate of Credit disbursed by Conventional Banks in Indonesia to small and medium business sectors (UMKM) in the 2011-2019 period. Meanwhile, the sharia side was used to explain the influence of Bank Indonesia Sharia Certificates (SBIS), inflation, and the BI Rate of Financing channeled by Islamic Banks in Indonesia to UMKM in the 2011-2019 period. The researcher employed a quantitative approach and analyzed the data using multiple linear regression analysis with two econometric models. Also, the data used in this study were secondary data obtained from official data from Bank Indonesia and the Financial Services Authority (OJK). The results of the conventional research partially show that Bank Indonesia Certificates (SBI) and inflation have a significant negative effect. In contrast, the BI variable Rate has a significant positive impact on UMKM credit in conventional banking. Simultaneously, it shows that there is a significant influence between the variables Bank Indonesia Certificate (SBI), inflation, and the BI Rate on lending to the UMKM sector in conventional banking. Furthermore, in terms of sharia, the results of the research partially explain that Bank Indonesia Sharia Certificates (SBIS) and BI Rate have a significant negative effect. In contrast, inflation has a significant positive impact on UMKM financing in Islamic banking. Simultaneously, it shows that there is a significant influence between the variables of Bank Indonesia Sharia Certificate (SBIS), inflation, and the BI Rate on the distribution of financing to the UMKM sector in Islamic banking.Keywords: SBI, SBIS, Inflation, BI Rate, and UMKM FinancingREFFERENCE Amaliawati, Lia. (2013). The influence of monetary policy (BI rate) on profitability of commercial banks in Indonesia. 10th UBAYA International Annual Symposium On Management.Boediono, (1995). Ekonomi makro. Yogyakarta: BPFE.Hafsah, Mohammad Jafar. (2004). Upaya pengembangan usaha kecil dan menengah (UKM). Jurnal Infokop, 25.Oktavina, Kritia dan Emile. (2012). Pengaruh kas, bonus SWBI (Sertifikat Wadiah Bank Indonesia), marjin keuntungan, dan dana pihak ketiga terhadap pembiayaan murabahah studi empiris pada bank umum syariah di Indonesia. Jurnal of Accounting and Investment, 13(1), 53-67.PBI. (2013). Fasilitas pendanaan jangka pendek bagi bank umum. Jakarta: Bank IndonesiaPBI. (2008). Sertifikat Bank Indonesia syariah. Jakarta: Bank IndonesiaPratama, Yoghi Citra. (2017). Analisis perbandingan pengaruh instrumen moneter syariah dan konvensional terhadap penyaluran dana ke sektor usaha mikro kecil dan menengah (UMKM) di Indonesia. Skripsi tidak diterbitkan. Jakarta: Universitas Islam Negeri Syarif Hidayatullah.Purwidianti, Wida dan Arini Hidayah. (2014).Faktor-faktor yang Mempengaruhi Alokasi Pembiayaan Perbankan Syariah untuk Usaha Mikro Kecil dan Menengah di Indonesia. Prosiding Seminar Hasil Penelitian LPPM UMP.Ramadhan, Masyitha Mutiara dan Irfan Syauqi Beik. (2013). Analisis Pengaruh Instrumen Moneter Syariah dan Konvensional Terhadap Penyaluran Dana ke Sektor Usaha Mikro Kecil dan Menengah (UMKM) di Indonesia. Jurnal al-Muzara’ah, 1(2), 175-190.Setianingsih, Diyan. (2018). Pengaruh inflasi, BI rate, sertifikat Bank Indonesia syariah dan financing to deposit ratio terhadap pembiayaan usaha mikro kecil dan menengah pada bank umum syariah dan unit usaha syariah di Indonesia periode 2014-2017. Skripsi tidak diterbitkan. Surakarta: Institut Agama Islam Negeri Surakarta.Undang-undang Nomor 20 Tahun 2008 tentang Usaha Mikro, Kecil, dan MenengahWahiduddin, Mohammad. (2018).Pengaruh inflasi, non performing financing (NPF) dan BI rate terhadap pembiayaan usaha mikro kecil dan menengah (UMKM) pada bank umum syariah 2012-2017. Al Amwal, 1(1), 76-89.